(3EOGQI GdETQGa GdOGNdj aj GdafGOb (B/s - (3jhSa, eUWais ((3YeGf (B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2016)
(3jVe eaghe hCfhGY GdafGOb,CgejI EOGQI GdETQGa GdOGNdj aj GdafGOb,GdJSdSd GdhXjaj dbSe EOGQI GdETQGa GdOGNdj(B((3eSDhdjGJ hegGe GdYGedjf(B)(3,eXgQ hSdhc GdYGedjf HbSe GdETQGa GdOGNdj,YdGbI EOGQI GdETQGa GdOGNdj HCbSGe GdafOb,JfXje GdYed HEOGQI GdETQGa GdOGNdj,GdSdGeI hGdCeGf aj bSe GdETQGa GdOGNdj,CfhGY GdZQa hGdCLfMI,COhGJ GdfXGaIs
(3HjHdjhZQGajG(B: (3U U(B.233-235s
Keywords: (3GdafGObs; (3GdafGOb(B- (3JfXje hEOGQI s